Prospettive di parità nella formazione e nel mercato del lavoro - Bianco, Adele
This volume aims to provide an overview of equal opportunities, particularly in the areas of higher and university education and the labor market. It is composed of different contributions and the result of an interdisciplinary reflection gained during the drafting of the Gender Report of the "Gabriele d’Annunzio" University (Chieti-Pescara, Italy). The text is proposed as a useful tool for training in this sector and as a sociological reflection on culture and the processes of construction of gender stereotypes